Pengaruh Keputusan Keuangan dan Struktur Kepemilikan terhadap Nilai Perusahaan - Akbar, Muhammad; Hindasah, Lela (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
This research examines the effect of financial decision (debt policy, dividend policy and investment) and ownership structure (insider ownership and institutional ownership) to firm value. This study used 96 firm-year samples of firms listed in Indonesian Stock Exchange during 2002 until 2006. Data are analyzed using multivariate regression method. The result of this research indicated that the debt policy, dividend policy, insider ownership are not significantly affect to the firm value. The effect of investment to firm value is positively significant but institutional ownweship is negatively significant.